MANAJEMEN PEMBIAYAAN PENDIDIKAN - Rusli, Rusdi; Kurniah Mutmainnah Nur; Sulkifli (As-Sulthan Journal of Education, 2025)
Educational finance management is an integral part of the education system aimed at managing financial resources effectively and efficiently to support the achievement of educational goals. This study discusses the concepts, principles, and practices of educational finance management across various levels, as well as its vital role in ensuring quality and equitable access to education. The process involves planning, budgeting, implementation, supervision, and evaluation of education funds from government, community, and other sources. This study also highlights various challenges, such as limited budgets, allocation disparities, and lack of transparency and accountability in fund management. With proper financial management, the education system is expected to be more responsive to students’ needs and the demands of the times. The study recommends strengthening the capacity of financial managers, increasing public participation, and optimizing the use of information technology to support transparent and sustainable education fund management.